Prospective associations between physical fitness and executive function in adolescents: The UP&DOWN study. (July 2022) - Muntaner-Mas, Adrià; Mora-Gonzalez, Jose; Cabanas-Sánchez, Verónica; Pintado, Laura Berninches; Salmon, Jo; Hillman, Charles H.; Castro-Piñero, Jose; Perales, José C.; Veiga, Oscar L.; Esteban-Cornejo, Irene
Abstract: Introduction: The objective of the present work is to investigate the prospective associations between physical fitness components (cardiorespiratory fitness, motor fitness, and muscular strength) and two domains of executive function (working memory and inhibitory control) in adolescents. Methods: A total of 422 Spanish adolescents (13.35 ± 1.54 years, at baseline) from the UP&DOWN study with assessments at baseline and at 2-year follow-up were included in the analysis. Physical fitness was assessed using the ALPHA Fitness Test Battery. Working memory was measured by the n-back task and inhibitory control by the go/no-go task. Relationships of physical fitness components with working memory and inhibitory control were examined using linear regression models, adjusted for confounders. Results: Higher baseline levels of the three physical fitness components (cardiorespiratory fitness, motor fitness, and muscular strength) individually predicted better performance on the working memory (βranged, from .159 to .207; all p < .012) and inhibitory control (βranged, from 0.168 to 0.263; all p < .004) tasks at the 2-year follow-up. Muscular strength was the only component associated with inhibitory control independent of the other 2 physical fitness components (β = 0.266; p = .005). Conclusions: All components of adolescents' physical fitness at baseline were individually associated with better working memory and inhibitory control at 2-year follow-up. Specifically, our results revealed that muscular strength was the component showing the strongest association with executive function, and even the only fitness component associated with inhibitory control independent of the other fitness components. These findings may have important public health and educational implication, since promoting exercise programs that improve physical fitness, and particularly, muscular strength, may positively inﬂuence cognitive health. Highlights: Higher levels of physical fitness predict better performance on working memory and inhibitory control. Muscular strength was the only component associated with inhibitory control. Muscular strength was the component showing the strongest association with both working memory and inhibitory control.